Barrett’s oESophagus trial 3 (BEST3): study protocol for a randomised controlled trial comparing the Cytosponge-TFF3 test with usual care to facilitate the diagnosis of oesophageal pre-cancer in primary care patients with chronic acid reflux - Offman, Judith; Muldrew, Beth; O’Donovan, Maria; Debiram-Beecham, Irene; Pesola, Francesca; Kaimi, Irene; Smith, Samuel G.; Wilson, Ashley; Khan, Zohrah; Lao-Sirieix, Pierre; Aigret, Benoit; Walter, Fiona M.; et al. (BMC cancer, 2018)
Early detection of oesophageal cancer improves outcomes; however, the optimal strategy for identifying patients at increased risk from the pre-cancerous lesion Barrett's oesophagus (BE) is not clear. The Cytosponge, a novel non-endoscopic sponge device, combined with the biomarker Trefoil Factor 3 (TFF3) has been tested in four clinical studies. It was found to be safe, accurate and acceptable to patients. The aim of the BEST3 trial is to evaluate if the offer of a Cytosponge-TFF3 test in primary care for patients on long term acid suppressants leads to an increase in the number of patients diagnosed with BE. The BEST3 trial is a pragmatic multi-site cluster-randomised controlled trial set in primary care in England. Approximately 120 practices will be randomised 1:1 to either the intervention arm, invitation to a Cytosponge-TFF3 test, or the control arm usual care. Inclusion criteria are men and women aged 50 or over with records of at least 6 months of prescriptions for acid-suppressants in the last year. Patients in the intervention arm will receive an invitation to have a Cytosponge-TFF3 test in their general practice. Patients with a positive TFF3 test will receive an invitation for an upper gastro-intestinal endoscopy at their local hospital-based endoscopy clinic to test for BE. The primary objective is to compare histologically confirmed BE diagnosis between the intervention and control arms to determine whether the offer of the Cytosponge-TFF3 test in primary care results in an increase in BE diagnosis within 12 months of study entry. The BEST3 trial is a well-powered pragmatic trial testing the use of the Cytosponge-TFF3 test in the same population that we envisage it being used in clinical practice. The data generated from this trial will enable NICE and other clinical bodies to decide whether this test is suitable for routine clinical use. This trial was prospectively registered with the ISRCTN Registry on 19/01/2017, trial number ISRCTN68382401 .